Factors affecting bone maturation in Chinese girls aged 4–8 years with isolated premature thelarche - Huiping Su; Zhe Su; Lili Pan; Li Wang; Zhongwei Xu; Gang Peng; Xianglei Li (BMC Pediatrics, 2020)
Abstract Background In isolated premature thelarche (IPT) girls, bone age (BA) is considered consistent with chronological age. However, some IPT girls confirmed by gonadotropin-releasing hormone (GnRH) stimulation test could show another trend. We analysed BA and possible potentiating factors in a selected group of girls aged 4–8 years with IPT. Methods IPT girls confirmed by GnRH stimulation test aged 4–8 years hospitalized from January 2015 to April 2018 at Shenzhen Children’s Hospital were included in this retrospective study. They were divided into two groups with advanced BA of 2 years as the cut-off. Body mass index (BMI) and hormone levels were the main outcome measures, and regression analysis was used to identify independent risk factors. IPT girls were divided into subgroups according to the levels of BMI standard deviation score (SDS), insulin-like growth factor-1 (IGF-1) SDS and dehydroepiandrosterone sulfate (DHEAS) SDS for comparisons of advanced BA. Results Overall, 423 subjects were included and classified into the advanced BA group (48.7%, n = 206) and control group (51.3%, n = 217). The advanced BA group had significantly higher BMI SDS, serum DHEAS SDS, IGF-1 SDS, androstenedione and fasting insulin and significantly lower sex hormone binding globulin (all p < 0.001). Serum IGF-1 SDS (OR = 1.926, p<0.001), BMI SDS (OR = 1.427, p = 0.001) and DHEAS SDS (OR = 1.131, p = 0.005) were independent risk factors for significantly advanced BA. In the multiple linear regression model, serum IGF-1 SDS, BMI SDS and DHEAS SDS were the strongest predictors of advanced BA, accounting for 19.3% of the variance. According to BMI, 423 patients were classified into three groups: normal weight (56.03%, n = 237), overweight (19.15%, n = 81) and obesity (24.82%, n = 105). The proportion of advanced BA in obesity group was significantly higher than those of normal weight and overweight groups (χ 2 = 18.088, p<0.001). In the subgroup with normal weight, higher serum IGF-1 SDS (p = 0.009) and DHEAS SDS (p = 0.003) affected BA advancement independent of BMI SDS. Conclusions Girls with IPT confirmed by GnRH stimulation test aged 4–8 years might have significantly advanced BA. Obesity was highly associated with advanced BA. Age-specific serum IGF-1 SDS and DHEAS SDS were risk factors for BA advancement independent of BMI.